(untitled) (Medical Forum Monthly, 2024)
Objective: To asses the safety, complication and results of edoscopic treatment of ureterocele. Study Design: Retrospective cohort study. Place and Duration of Study: This study was conducted at the Urology Department CMCH Larkana and Khairpur Medical College Hospital, Khairpur from June 2011 to January 2014. Materials and Methods: 22 cases of ureterocele at Urology Department CMCH Larkana and Khairpur Medical College Hospital Khairpur was conducted. Standard method of endoscopic surgery like endoscopic deroofing in adults and endoscopic incision in children carried out. Results: Out of 22 patients, 12 (54.5%) were female and 10(45.5%) male. The age of the patients ranged from 5 to 30 years. Mean age of patients were16.3with SD±8.7 The presenting features were lumbar pain in 17(77.3%) cases, urinary tract infection in 3(13.6%), and in 2(9.1%) cases it was detected incidentally. All patients successfully treated by endoscopic surgery. Minor complication occurs like haematuria and UTI in 5(22.7%), which treated medically. Conclusion: Endoscopic treatment for ureterocele is safe and cost effective surgery and least post operative complication.